Problematika Peraturan Mahkamah Konstitusi dan Implikasinya - Adam Ilyas; Dicky Eko Prasetio (The Constitutional Court of the Republic of Indonesia, 2022)
The position of the Constitutional Court Regulation (PMK) in the hierarchy of laws and regulations is not strictly regulated, so it is not known where it is located, or which institution has the right to conduct a judicial review of it. Therefore, this study will examine three things, namely: (i) the position of PMK; (ii) the implications of PMK that have not been promulgated; and (iii) the institution entitled to conduct a judicial review of PMK. The research method used is the normative legal research method. The result is that PMK has a